Paradoxical lymphadenopathy during treatment of cavitary tuberculosis in an immunocompetent patient - Rakotoson, J L; Rakotomizao, J R; Andrianasolo, R L; Rakotoharivelo, H; Andrianarisoa, A C F (Revue de pneumologie clinique, 2011)
The paradoxical reactions during antituberculosis treatment are defined as a transient, clinical and/or radiological increase in preexisting tuberculous lesions or as the emergence of new symptoms, while treatment is adapted and correctly taken. The authors report a case of paradoxical left axillary lymphadenopathy during the treatment of cavitary tuberculosis, which appeared after seven months of treatment. No consensus on the therapeutic management of this entity has been developed to date but many authors propose an extension of antituberculosis treatment, a short corticosteroid therapy, an aspiration puncture and/or a surgical excision of the lymphadenopathy.